Penerapan activity-based costing sebagai dasar perhitugan biaya pada Aisyah Laundry - Maharany H., Sylvya Dewanty; Alexander, Stanly W.; Maradesa, Djeini (Riset Akuntansi dan Manajemen Pragmatis, 2025)
This study aims to apply the Activity-Based Costing (ABC) method as a basis for service cost calculation at Aisyah Laundry, a micro-scale laundry service business. The study employs a qualitative research design with a case study approach, focusing on an in-depth analysis of cost structures and operational activities. Data were collected through interviews, direct observation, and documentation to identify activities, classify cost pools, determine cost drivers, and calculate service costs based on resource consumption. The results show that the ABC method provides a more detailed and accurate representation of service costs compared to the traditional costing method previously used by the business. The calculated cost per kilogram for washing and ironing services is IDR 2,948, while the cost for ironing-only services is IDR 1,523 per kilogram. When compared to the prevailing service rates, the findings indicate that Aisyah Laundry is still operating profitably. The implementation of the ABC method enables a clearer understanding of cost behavior and supports more rational pricing decisions, cost control, and operational efficiency. This study demonstrates that Activity-Based Costing is a relevant and effective costing approach for micro enterprises in the laundry service sector.